PENGARUH BIMBINGAN BELAJAR MENGGUNAKAN MEDIA INTERNET TERHADAP PENYELESAIAN TUGAS PELAJARAN SISWA SMP NEGERI 5 TEBING TINGGI - Lily Rosidah; Taty Fauzi; Endang Surtiyoni (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine a) tutoring services in schools carried out by Guidance and Counseling teachers, b) students' ability to use the internet as a learning medium in completing lesson assignments and c) obstacles felt by students in completing assignments. study. The phenomenon of students' difficulties in completing lesson assignments is related to the ability to use the internet, in the new normal learning era. Asample of 38 students in class X SMP Negeri 5 Tebing Tinggi. Data obtained through interviews and questionnaires and analyzed using t test. Normality of the data using the Liliefors test with a significance level of 0.05 L table = .1437. The test criteria show the value of Lo < Ltable or 0.0680 < 0.1437, the data is normally distributed. While the results of hypothesis testing, obtained tcount > ttable or 15,499 > 1,697 Ha is accepted and H0 is rejected. The average posttest score after tutoring is done, the results of the completion of the task are in a good category (77.80) thus the hypothesis states that